Identification and expression profiling of the bone morphogenetic protein gene family based on pearl culture in mantle and visceral mass of Hyriopsis cumingii - Chen, Yiwen; Liu, Shijun; Yao, Yuanbin; Sun, Junlin; Chen, Xiaofeng; Yu, Xiangyang; Xuan, Xingrong; Bian, Xiangli; Li, Wenjuan (Frontiers in Veterinary Science, 2024)
Bone morphogenetic proteins (BMPs) play an important biological role in pearl biomineralization in pearl mussels. In this study, based on the genome data of the triangular sail mussel (Hyriopsis cumingii), the genome-wide identification and bioinformatic analysis of BMP gene family were performed, and the expression pattern of the BMP genes was investigated by the insertion experiments. The results showed that a total of 12 BMP gene family members (BMP2a/2b, BMP3, BMP5a/5b, BMP7a/7b/7c, BMP9, BMP10a/10b, and BMP11) were identified, which were unevenly distributed on chromosome 3/14/18, encoding 169–583 amino acids, with molecular weights ranging from 19.32 to 65.99 kDa. BMP2a, BMP7b, and BMP10a were distributed, respectively, in the cytoplasm, endoplasmic reticulum and mitochondria, others were distributed in the nucleus. qRT-PCR results showed the significant tissue specificity in BMPs gene expression. The HcBMPs were differentially expressed in the mantle and visceral mass, and the expression level was higher in the visceral mass. The expressing trends of HcBMPs were not consistent between the mantle and visceral mass insertion, suggesting that HcBMPs may perform different functions. We also found that insertion surgery in the mantle and visceral mass significantly alters the expression profiling of the BMP gene family. Insertion of the mantle induced the biomineralization function of BMP2a, BMP7a, and BMP7b, while BMP3 and BMP10b played opposite roles in visceral mass insertion. Visceral mass insertion could suppress BMP9 expression at 5 d and BMP5b expression at 90 d after insertion This work lays the foundation and data support for the preliminary elucidation of regulatory role and mechanism of HcBMPs in the pearl-cultivating process of mantle and visceral mass.